Features Of Optical And MagnetoOptical Spectra Of Rare-Earth Ions Ho3+ And Tb3+ In Garnet Crystals (Eurasian Journal of Physics,Chemistry and Mathematics, 2024)
The article is devoted to the analysis of the results of experimental and theoretical studies of the relationship between magneto-optical and optical-magnetic effects with the features of the Stark structure of the energy spectra of non-Kramers RE ions in garnet crystals.